2002
DOI: 10.1007/bf03020532
|View full text |Cite
|
Sign up to set email alerts
|

Regional blood flows are affected differently by PEEP when the abdomen is open or closed: An experimental rabbit model

Abstract: Objective: The study of induced circulatory changes requires simultaneous assessment of multiple regional circulations because of interactions and compensatory mechanisms. Positive end expiratory pressure mechanical ventilation (PEEP) is known to cause marked, and potentially deleterious, cardiovascular changes. Our aim was to use a comprehensive approach to assess PEEP-induced circulatory changes in open vs closed abdomen animals. Material and methods:In the anesthetized rabbit, we used implantable Doppler mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…9 RBF is primarily affected by PEEP because of sympathetic activation related to increased plasma renin activity. 29 Results of other studies 9,35 have also suggested that although total RBF is relatively unchanged, blood flow is redistributed from the cortical to the juxta medullary nephrons. This redistribution would be associated with decreased urine output, decreased creatinine clearance, and an increased fractional resorption of sodium 35 ( Figure 4).…”
Section: Cardiopulmonary Dynamicsmentioning
confidence: 94%
See 2 more Smart Citations
“…9 RBF is primarily affected by PEEP because of sympathetic activation related to increased plasma renin activity. 29 Results of other studies 9,35 have also suggested that although total RBF is relatively unchanged, blood flow is redistributed from the cortical to the juxta medullary nephrons. This redistribution would be associated with decreased urine output, decreased creatinine clearance, and an increased fractional resorption of sodium 35 ( Figure 4).…”
Section: Cardiopulmonary Dynamicsmentioning
confidence: 94%
“…22 Positive end-expiratory pressure (PEEP) may reduce cardiac output by causing a further increase in intrathoracic pressures, which compresses the pulmonary vasculature. 29 This change increases right ventricular afterload, leading to a decrease in emptying and ultimately a decrease in left ventricular preload. [29][30][31][32] Left ventricular distensibility also decreases, with an associated decrease in left ventricular function, especially with PEEP greater than 15 cm H 2 O.…”
Section: Cardiopulmonary Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the reduced output from the right ventricle leads to a reduced stroke volume in the left ventricular and a reduction in cardiac output [ 10 ]. Decreased cardiac output affects the cerebral circulatory system by increasing intracranial pressure and reducing cerebral perfusion pressure and thereby reducing cerebral blood flow [ 11 ].…”
Section: Introductionmentioning
confidence: 99%